2014
DOI: 10.1115/1.4028171
|View full text |Cite
|
Sign up to set email alerts
|

“Where Are We Now and Where Are We Going?” The BioM Innovation Database

Abstract: We present the BioM Innovation Database, the first of its kind containing detailed information about global biomimetic activity. We present a quantitative and qualitative analysis of the database to address the following questions: (1) Are products, which are identified as being the result of biologically inspired design (BID), actually BID and to what extent do they use biomimicry terminology in their descriptions by the designers? (2) To what extent do BID products mimic the forms, processes and interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 37 publications
0
72
0
Order By: Relevance
“…According to Jacobs et al, 3 some of the reasons which account for the small number of biomimetic products on the market is the lack of a clear method, 4 the difficulties of interdisciplinary work and the complexity of biology as a model. In line with these aspects, studies on teaching students in biomimetics have shown key challenges with the process -that is, communication across discipline boundaries, analysis of problems to solve and identification and understanding of biological systems.…”
Section: Challenges For Biomimetics In Practicementioning
confidence: 99%
See 4 more Smart Citations
“…According to Jacobs et al, 3 some of the reasons which account for the small number of biomimetic products on the market is the lack of a clear method, 4 the difficulties of interdisciplinary work and the complexity of biology as a model. In line with these aspects, studies on teaching students in biomimetics have shown key challenges with the process -that is, communication across discipline boundaries, analysis of problems to solve and identification and understanding of biological systems.…”
Section: Challenges For Biomimetics In Practicementioning
confidence: 99%
“…2 On the other hand, the number of commercially available biomimetic products is rather low (of 303 biomimetic cases, 28% are commercially available, 60% are in development, 8% are concepts and 2% are discontinued). 3 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations